Instagram Social Media Marketing Communuication Strategy @CRSL.Concert Yogyakarta Series #4 in Builiding Brand Awareness in 2023 - Mia Winani; Ishak, Aswad (Jogjakarta Communication Conference (JCC), 2025)
This research analyzes the social media marketing communication strategy of Instagram @crsl.concert Yogyakarta series #4 in building brand awareness in 2023. This research describes the social media marketing communication strategy of Instagram @crsl.concert Yogyakarta series #4 in building brand awareness in 2023. This research method is descriptive qualitative, which describes the research conditions based on actual data. The object of this research is Instagram social media marketing communication strategy @crsl.concert Yogyakarta series #4 in building brand awareness in 2023. The results of the research on Instagram social media marketing communication strategy @crsl.concert Yogyakarta series #4 in building brand awareness in 2023 have been carried out based on the process of digital marketing including accessibility, interactivity, entertainment, credibility, irritation and informativeness. Through the utilization of social media, @crsl.concert has succeeded in building strong brand awareness through Instagram and has reached the top of mind stage among audiences.